Preferred social media platforms in tourism industry in Johor using best worst method / Ummi Nur Shafina Abu Bakar, Rohaizan Ramlan and Rashidah Mokhtar - Abu Bakar, Ummi Nur Shafina; Ramlan, Rohaizan; Mokhtar, Rashidah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Despite global economic fluctuations, the travel and tourism industry are gradually expanding. However, the pandemic has created many obstacles for the tourism industry. Due to COVID -19, although there is still a strong desire to travel, demand is low as most domestic travellers are more cautious in their travel intentions. However, social media able to help disseminate information and credible advice. Thus, it is important to determine the preferred social media platform used by the travel agency (TAs) and the selection of social media platform based on demographic. The scope of this study is limited to the local travel agencies in Johor. This study uses a quantitative method with convenience sampling to collect the data and then analysed using the Best-Worst Method (BWM). 110 responses were received from the respondents of each company. However, 10 of the responses were rejected because the value of CR was above the associated threshold value of 0.2306. The results show that the most preferred platform is Facebook and the least preferred is Twitter. The details of the outcome can be found in the paper. Some recommendations are made for TAs, such as using post scheduling tools, management tools and analytics tools to help them post their content daily, manage their social media accounts more effectively and analyse social media engagement.